Entrepreneurship skills framework for fostering the employability of industrial technology students - Sunday, Olojuolawe Rufus; Olusola, Osuntuyi Edward; Bamidele, Ibidapo Abel; Olalekan, Adegboye Oluwadamilola (International Journal of Evaluation and Research in Education (IJERE), 2024)
The rising rate of youth unemployment and its attendant consequences on the general populace in Nigeria has assumed a frightening dimension. The academia and other relevant stakeholders have gradually come to realize that the possession of academic qualifications alone cannot guarantee a good quality job. Nigerian higher intuitions are now introducing entrepreneurship studies in their school curriculum without a clear framework. Research has shown that this does not guarantee total graduates unless we have an entrepreneurship skills framework that is functional and discipline-based. Noting that entrepreneurship is classified into two folds; entrepreneurship specific and entrepreneurship mindset, this study intends to develop an entrepreneurship skills framework that will promote the employability of the students of Electrical Technology in Colleges of Education in Nigeria. The survey research that employs the sequential exploratory mixed methods was used for the study. The population for this phase consists of entrepreneurs and academics in Nigeria. The use of the partial credit model in the Rasch analysis model guaranteed the consensus of the experts on each of the items being measured. The outcome of the study will contribute to the social-economic peace and sustainability in Nigeria and the body of knowledge in entrepreneurship regarding electrical technology.